Body composition and segmental bioimpedance phase angle in elite volleyball players - Di Vincenzo, O.; Marra, M.; Sammarco, R.; Speranza, E.; Scalfi, L. (Proceedings of the 7th International Conference on Sport Sciences Research and Technology Support icSPORTS - Volume 1, 2019)
Because of the great interest in the evaluation of body composition (BC) in athletes, this study aimed to estimate BC variables like fat-free mass (FFM) and fat mass (FM) of volleyball players compared to a group of healthy subjects. 12 female volleyball players (VP, age 23.8 ± 3.6 years; weight 63.0 ± 5.1 kg; stature 170 ± 4 cm; BMI 21.9 ± 1.3 kg/m2) and 22 healthy females as control group (CG, age 23.6 ± 2.0 years; weight 60.7 ± 4.8 kg; stature 167 ± 5 cm; BMI 21.9 ± 1.3 kg/m2), participated to the study. BC was evaluated by skinfold thickness and whole-body and segmental bioimpedance analysis (BIA) measurements were assessed. BC resulted significantly different in VP than CG (FM (kg) = 15.7 ± 2.7 vs. 18.0 ± 3.0, p=0.036; FM (%) = 24.8 ± 3.0 vs. 29.5 ± 3.8, p=0.001; FFM (kg) = 47.4 ± 3.5 vs. 42.8 ± 3.6, p=0.001). These data confirm previous observations on FM % in VP. Moreover, assessing segmental BIA-derived phase se angle (PhA) appears to be sensible in these evaluations.